Two decades of family planning in Ethiopia and the way forward to sustain hard-fought gains! - Mengistu Asnake Kibret; Lia Tadesse Gebremedhin (BMC, 2022)
Abstract Family planning (FP) is a human right, and ensuring women's access to FP is central to protecting the health and wellbeing of mothers and children. Over the past two decades, Ethiopia has made FP service more widely available, increasing the contraceptive prevalence rate from 8% in 2000 to 41% in 2019. This remarkable fivefold increase can be attributed to the country's overall development, including investment in education (particularly for girls) and reduction in child marriage, as well as the adoption and implementation of several enabling FP policies and strategies. In Ethiopia, achieving universal access to sexual and reproductive health care services, information, and education, including FP, by 2030 means enhancing these effective government policies and programs. Achieving universal access requires increasing financial resources, including domestic financing through greater government commitment for commodity security and program implementation; strengthening public-private partnerships; and improving service delivery for populations that are hard to reach and/or in humanitarian crisis. The persistence of equity gaps due to regional and/or sociodemographic disparities and the low quality of FP service delivery challenge our progress in Ethiopia. The papers included in this supplement provide additional detail on the overall progress described in this commentary and highlight focal areas for improvement in responding to unmet needs. Current policies and services must adapt, maintain, and build upon these gains and focus on targeted actions in areas identified for improvement. We must sustain the hard-fought gains of the past decades and help shape the prosperous future we advocate for in our society by 2030 and beyond-Leaving No One Behind.